1994
DOI: 10.1080/1057356940100405
|View full text |Cite
|
Sign up to set email alerts
|

Expressive Journal Writing for Comprehending Literature: A Strategy for Evoking Cognitive Complexity

Abstract: Whereas traditional reading instruction methods advocate text-based questions to guide students' thinking from literal comprehension to critical understanding of text, reader-based instruction promotes the use of journal writing for guiding comprehension. Through response journals, students are able to construct their own meaning of the text, making connections between the text and their own lives. We conducted a study in 11th-grade literature classes to determine the types and depths of cognitive complexity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…For example, Klein (1999) in concurring with the general findings of the other reviews, noted that various studies (Durst, 1987;Langer & Applebee, 1987;Schumacher & Nash, 1991) reported mixed conclusions on the value of analytical writing. Similarly, research studies on personal, journal writing (MacDonald & Cooper, 1992;Mulchay-Ernt & Ryshkewitch, 1994;Newell, Suszymski, & Weingart, 1989) only provided ambiguous support for the value of this genre for learning. As Klein (1999) observed, a further problem with most of these studies was that they failed to provide a detailed account of the classroom context or the teacher's method or focus of instruction, and therefore provided very limited evidence of the effects of these factors on student learning.…”
Section: Debates Over Different Kinds Of Writing To Serve Learningmentioning
confidence: 92%
“…For example, Klein (1999) in concurring with the general findings of the other reviews, noted that various studies (Durst, 1987;Langer & Applebee, 1987;Schumacher & Nash, 1991) reported mixed conclusions on the value of analytical writing. Similarly, research studies on personal, journal writing (MacDonald & Cooper, 1992;Mulchay-Ernt & Ryshkewitch, 1994;Newell, Suszymski, & Weingart, 1989) only provided ambiguous support for the value of this genre for learning. As Klein (1999) observed, a further problem with most of these studies was that they failed to provide a detailed account of the classroom context or the teacher's method or focus of instruction, and therefore provided very limited evidence of the effects of these factors on student learning.…”
Section: Debates Over Different Kinds Of Writing To Serve Learningmentioning
confidence: 92%
“…In precollege work, one of the most common forms of writing to learn is done by informal personal journal responses related to educational experiences such as literary readings, scientific experiments, videos, or from discourse with others (Kahaney & Heinrich, 1994; Keys et al, 1999; Martin, 1992; Mulcahy‐Ernt & Ryshkewitch, 1994). The process of writing journals helps with the process of understanding relationships among ideas, knowledge transformation, and construction of new meaning (Klein, 1999; Wallace, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%